What Are the Regulatory Considerations for AI Telemedicine? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2019)
Artificial intelligence (AI) is rapidly transforming the healthcare landscape, and its integration into telemedicine is creating unprecedented opportunities ...
Keywords: Telemedicine and Digital Health; Regulatory; Considerations; Telemedicine; Artificial Intelligence; Machine Learning; Healthcare